KONDISI PANAS DI DALAM HUTAN KOTA: STUDI KASUS DI AREA DANAU UNIVERSITI SAINS MALAYSIA - Saputra, Riswan Hadi (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2023)
Open space in urban areas has an important meaning for the community. Because most people will spend time resting and recreation in that place to relieve stress in activities. One of the open spaces is tropical urban forest on USM lake. Trees are one of the important features in open space, because trees affect the comfort of the place, so that in planning the type of tree must be chosen according to the surrounding environment. Logging of thermal conditions with temperature and relative humidity parameters was carried out to determine the thermal conditions of the lake USM environment and calculate the THI values of three different tree species to find out which tree could best influence the thermal environment conditions. The study was conducted in January 2023, at USM Lake on sunny days. From the results of research, the average condition of the USM lake thermal environment is 31°C for temperature and 62.5% for Relative humidity, this result is almost the same as the thermal environmental conditions in previous studies. For THI calculations, the tree that has the best THI is Samane Saman, with 26.8°C then followed by Andira Inermis tree with 26.9°C and finally Petrocarpus Indicus with 27.2°C. knowledge of the thermal environmental conditions and species of trees is a very important part in building and developing open spaces in order to provide thermal comfort for people who come to rest and recreation.